Inflation Pressures And International Financial System Dynamics: Evidence From Three High Inflation G20 Economies - Rangkuty, Dewi Mahrani; Syafii, Muhammad; Hasyim, Sirojuzilam (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
Using a simultaneous equation approach, this study examines the international financial system in three G20 member countries with the highest inflation rates, namely Argentina, Turkey, and Russia. The analysis focuses on the interaction between key macroeconomic variables, including inflation, exchange rates, money supply, imports, and interest rates. Secondary data covering the period 2013–2022 were obtained from the World Bank and Trading Economics. A simultaneous equation model was employed as the analytical method, using EViews 12 as the estimation tool. The empirical results indicate that inflation exerts a positive and persistent influence on exchange rate depreciation in the long run across the three countries. In addition, changes in money supply and interest rates significantly affect inflation dynamics and exchange rate stability, while imports contribute to inflationary pressures through higher import prices. These findings highlight the importance of effective and coordinated monetary policy in managing inflation and maintaining exchange rate stability, particularly in G20 countries experiencing high inflation episodes.